Prevalence of hypertension and its significant correlates among Bangladeshi adults: a quantitative analysis from City Corporation Rangpur, Bangladesh - Das, Sukanta; Chakravorti, B. K.; Islam, Sahebul (International Journal Of Community Medicine And Public Health, 2019)
Background: Hypertension (HTN) is a common medical problem and the premier risk factor for cardiovascular disease. Hypertension is growing at a faster rate among all aged population. Therefore, this study aimed to investigate the prevalence of hypertension and to identify the significant risk factors of hypertension among the respondents. Methods: The sample of 1302 randomly selected respondents of various government offices at Rangpur City Corporation, Bangladesh are taken for this study. Hypertension was defined by the systolic blood pressure reading above 140 or the diastolic reading above 90 mmHg. Pre-hypertension was defined by the systolic blood pressure reading 120-139 or the diastolic reading 80-89 mmHg. Prevalence and risk factors of hypertension are presented as percentages. The significant association between the categorical variables is measured using Chi-square test. Results: It is found that the prevalence of hypertension and pre-hypertension (stage-1 HTN) among the respondents are 25% and 54%, respectively. Most of the respondents are in the pre-HTN stage, and at any time they may fall under hypertension. Respondent’s age, gender, residence, smoking habit, and physical activity are found as significant factors of hypertension. Conclusions: Reliable information about the prevalence of hypertension and its associated risk factors is very essential for growing awareness, treatment, and control of hypertension. Prevalence of hypertension is high among the study subjects. The male respondents who are at the higher age group, residing in the urban area, not taking regular physical exercise, and having smoking habit are found more prevalent cases of hypertension than the other counterparts.